Liver metastases in gastroenteropancreatic neuroendocrine tumours – treatment methods - Gut, Paweł (Gastroenterology Review/Przegląd Gastroenterologiczny, 2020)
Surgical approaches that allow the safe treatment of multiple, bilateral, large tumours, and that combine extirpative, ablative and interventional therapies, have expanded the population of patients with neuroendocrine tumors (NET) liver metastases (LMs) who can benefit from aggressive treatment of their liver disease. Pre-treatment staging often includes the biochemical assessment of serologic markers such as serotonin, insulin, vasoactive intestinal peptide, and chromogranin, even in patients without clinically apparent hormonal excess. Radiofrequency ablation (RFA) is a technique that involves the use of thermal energy to induce coagulation necrosis, thereby destroying tumour cells. Resection plus RFA is increasingly used in patients with bilateral NET LMs. Resection is performed for large or dominant lesions, while ablation is used to treat small lesions. Hepatic arterial embolization, typically termed transarterial embolization, and transarterial chemoembolization have been shown to induce a reduction in tumour size and to ameliorate symptoms of excess hormonal secretion.